The Role Of Institutional Quality, Foreign Direct Investment, And Country Size On Trade Openness In The ASEAN-6 Region - Wahyu Aji Wijaya; Azwardi; Abdul Bashir (Journal of Economic Development, Environment and People, 2023)
The current development of globalization has led to a very fundamental transformation in the economic system. the phenomenon of globalization cannot be avoided by any country, moreover countries that previously isolated it from the outside world cannot be avoided either. Therefore any country will still be affected by globalization, so that it will create international trade that is increasingly spreading from every country. This study aims to analyze the role of institutional quality through government effectiveness and regulatory quality, foreign direct investment, and country size on trade openness in the ASEAN-6 region during the 2002-2021 period using panel data analysis techniques. in using the panel data technique based on the best testing through the Chow test and the Hausman test that the best model used in this study is the Fixed Effect Model (FEM) which shows the variables of government effectiveness and investment directly have a positive and significant effect on trade openness. while the quality of regulations and country size have a negative and significant effect on trade openness in the Asean Region.